Public Sector Performance: The Impact of Transformational Leadership and Public Service Motivation on Organizational Performance as mediated by Organizational Commitment - Sentoso, Antony; Mardiana, Asri; Yulfiswandi, Yulfiswandi (Dinasti Publisher, 2025)
With organizational commitment as mediating variable, the objective of this study is toexamine and evaluate the impact of public service motivation and transformational leadershipon organizational performance. Respondents from the public sector of Maritime Affairs andFisheries Service Branches dispersed around the Riau Island Province Region make up thisquantitative research technique with data processing using Smart PLS. Completing aquestionnaire sent via Google form was the main method of gathering primary data for thisproject. According to the study's results, transformational leadership has a significantinfluence, but Public service motivation has little impact on organizational performance.Organisational commitment is essential for mediating the relationship betweentransformational leadership and organizational performance, as well as public servicemotivation and organizational success.